2012
DOI: 10.1007/s12070-012-0541-6
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal Dacryocystorhinostomy with Mucosal Flaps: Our Experience

Abstract: The endoscopic dacryocystorhinostomy (DCR) has distinct advantage over external DCR. There is no ugly scar on the face, less intraoperative bleeding, it is a daycare procedure and patient is discharged on the same day evening. Endoscopic DCR is considered to be a superior alternative technique to the conventional external DCR. Patients diagnosed with nasolacrimal duct obstruction between Jan 2009 and Jan 2011 were included in the study. One hundred and twenty endo DCR were performed with conventional 'cold ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
8
0
4
Order By: Relevance
“…Our median follow-up period was 15 During follow-ups, recurrences were seen in one patient both in Groups 1 and 2, and 6 patients in Group 3. No recurrence was seen in 80.5% of the patients participated in the study while 19.5% of the patients experienced recurrences.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our median follow-up period was 15 During follow-ups, recurrences were seen in one patient both in Groups 1 and 2, and 6 patients in Group 3. No recurrence was seen in 80.5% of the patients participated in the study while 19.5% of the patients experienced recurrences.…”
Section: Resultsmentioning
confidence: 98%
“…[1] In the literature, surgical success was defined as elimination of complaints of epiphora within the first postoperative year and demonstration of a patent lacrimal system using lacrimal system lavage and endoscopic examination. [15] In their study, Tsirbar and Wormald expressed the secret of a successful DCR procedure as nearly complete excision of the bone tissue covering lacrimal sac and its approximation with mucosal flap constructed from nasal mucosa by marsupialization of lacrimal sac mucosa. [16] Liang et al indicated that excision of bony processes surrounding newly-constructed ostium in order to create a cavity with a smooth surface increases surgical success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Большинство исследователей считают, что высокую эффективность при ДЦР можно достичь путем выкраивания лоскута из медиальной стенки слезного мешка [6,16,17]. Однако форма выкроенного лоскута и его расположение в полости носа различаются.…”
Section: формирование лоскутов слезного мешкаunclassified
“…A. Majumder и соавт. [6] откидывали лоскут в форме буквы «U», созданный из медиальной стенки слезного мешка. Положительный результат после операции был получен в 93% случаев.…”
Section: формирование лоскутов слезного мешкаunclassified
See 1 more Smart Citation